Impact of indoxacarb and sulphur formulation on aphid and three specific predators in Okra fields - Gesraha, M. A. (2023)
Application of indoxacarb and sulphur formulation in Okra fields to control aphid was carried out. The adverse effects of these applications against some important predators were investigated. The obtained results revealed that indoxacarb was more effective than sulphur application in all treatments. At the end of the experiment, the percentages of population reductions of Coccinella indoxacarb treatment reached ≈ 92 and 76% for larvae and adults, respectively. The corresponding figures for Chrysoperla were ≈ 79 and 82% for larvae and adults, respectively. Indoxacarb-induced reduction in the Paederus population reached about 80%, while sulphur formulation had negative effects. Both indoxacarb and sulphur formulations were harmful to the aphid, inducing about 97 and 26% reduction, respectively, for the mean number of aphid populations.